Alopecia universalis during treatment with leflunomide and adalimumab - Case report - Rosana Lazzarini; Gabriela Cunha Capareli; Roberta Buense; Rute Facchini Lellis (Sociedade Brasileira de Dermatologia, 2014)
Alopecia areata is a non-scarring form of alopecia that can be localized or widespread. Its etiology is unknown, but immunological factors are implicated in its pathogenesis. With the more frequent use of anti TNFα biologic drugs, some alopecia areata cases during their use have been described. We report a case of universal alopecia in a patient with rheumatoid arthritis while using adalimumab and leflunomide.